THE DESIGN APPLICATION OF PHYSICAL OUTCOME’S THEORY ON THE HOSPITAL OF MOTHER AND CHILD IN SURAKARTA - Glabella Ersyara Ramadhani; Ahmad Farkhan; Leny Pramesti (Universitas Sebelas Maret Surakarta, 2018)
Women and Children Hospital is an useful healthcare facility to improve the health of Indonesian people especially for women, mothers and children. The lack of adequate health facilities in Indonesia for mothers and children, especially in the city of Solo, makes the number of health cases concerning them are still poorly handled and thorough. Therefore, it needs a special health facility that handles the problem, namely Women and Children Hospital with concept that can solve the problem. The appropriate theory for solving the problem is the Physical Outcome Theory (derived from the concept of Healing Environment).That theory serves to help patients in the hospital, to feel comfortable and safe to be treated in it. The research method used is applied research, through the exploration of initial ideas and data collection which then concluded to be a guide in the design analysis. The results of Physical Outcome Theory implementation in buildings, realized through the processing siteplan design, building facade, interiors, and exteriors.